Environmental maintenance with effective and useful zoning to protect patients and medical staff from COVID‐19 infection. Issue 1 (13th July 2020) - Ogawa, Fumihiro; Kato, Hideaki; Sakai, Kazuya; Nakamura, Kana; Ogawa, Mizuki; Uchiyama, Munehito; Nakajima, Kento; Ohyama, Yutaro; Abe, Takeru; Takeuchi, Ichiro
Abstract : Aim: The coronavirus disease 2019 (COVID‐19) pandemic has accelerated all over the world, and global health‐care systems have become overwhelmed with potentially infectious patients seeking testing and care. It is essential to set up effective and useful zoning to prevent the spread of infection to and from medical staff or other patients with effective use of standard precautions with personal protective equipment (PPE). Methods: We repurposed a general ward into an acute care unit for severe COVID‐19 patients taking into consideration airflow, the direction of movement of medical staff, and prevention of the spread of infection to medical staff and other patients. We checked the daily condition and body temperature of all medical staff for 60 days. Results: There was no evidence of COVID‐19 infection in any medical staff or other patients during the period thanks to effective and useful zoning with PPE. Conclusion: Special wards and rooms should be set up for future protection of medical staff and other patients, and prevent the explosion of COVID‐19 infection with effective and useful zoning with PPE. Abstract : It is very important for us to set up the special wards and rooms with some devices for the time to come due to protect healthcare staffs and other patients, and prevent from the explosion of COVID‐19 anywhere with effective and useful zoning.